Incidence, Predictive Factors, and Prognostic Impact of Silent Atrial Fibrillation After Transcatheter Aortic Valve Implantation - Robert, Raphael; Porot, Guillaume; Vernay, Clémence; Buffet, Philippe; Fichot, Marie; Guenancia, Charles; Pommier, Thibaut; Mouhat, Basile; Cottin, Yves; Lorgis, Luc (The American Journal of Cardiology, 2018)
New onset atrial fibrillation post-transcatheter aortic valve implantation (TAVI) is common and is associated with adverse outcomes. However, silent atrial fibrillation (AF) is poorly documented in the context. This study sought to evaluate the incidence, predictive factors, and prognostic value of Silent AF post-TAVI. All the consecutive patients with TAVI were prospectively analyzed by continuous electrocardiogram monitoring≥48 hours after implantation. Silent AF was defined as asymptomatic episodes lasting at least 30 seconds. The population was divided into 3 groups: history of AF, no-AF, and silent AF. Among the 206 patients implanted with TAVI, 19 (16.1%) developed silent AF. Compared with the no-AF group, patients with silent AF shared the same clinical characteristics and cardiovascular risk factors. Procedural success and echography parameters after the device implantation were similar between groups. Left atrial volume was significantly increased (p <0.001) in the silent AF group, together with preimplantation C-reactive protein (CRP) >3 mg/L and glucose (p = 0.048 and p = 0.002). By multivariate analysis, CRP >3 mg/dl and logistic European System for Cardiac Operative Risk Evaluation were identified as independent predictors of silent AF. In-hospital and 1-year mortalities were higher in pre-existing AF patients, whereas no-AF and the silent AF patients share the same prognosis. Our prospective study showed for the first time that silent AF is frequent after TAVI procedures. In conclusion, our work suggests that CRP could help to predict the risk of developing silent AF. However, the onset of silent AF is not associated with worse prognosis in the year following the procedure in our study.